Selected fluorescent techniques for identification of the physiological state of individual water and soil bacterial cells - review - Lew, S; Lew, M; Mieszczyński, T; Szarek, J (Folia microbiologica, 2010)
Stimulated by demands of the natural environment conservation, the need for thorough structural and functional identification of microorganisms colonizing different ecosystems has contributed to an intensive advance in research techniques. The article shows that some of these techniques are also a convenient tool for determination of the physiological state of single cells in a community of microorganisms. The paper presents selected fluorescent techniques, which are used in research on soil, water and sediment microorganisms. It covers the usability of determination of the dehydrogenase activity of an individual bacterial cell (CTC+) and of bacteria with intact, functioning cytoplasmic membranes, bacteria with an integrated nucleiod (NuCC+) as well as fluorescent in situ hybridization (FISH).
Keywords: Bacteria; Water Microbiology; fyziologie bakterií; techniky typizace bakterií; Soil Microbiology; fluorometrie; půdní mikrobiologie; Bacterial Physiological Phenomena; In Situ Hybridization, Fluorescence; mikrobiologie vody; Fluorometry; Bacterial Typing Techniques; Bacterial Proteins; hybridizace in situ fluorescenční; bakteriální proteiny